Penyuluhan pentingnya pengukuran status gizi dalam upaya pencegahan stunting - Athiah, Medina; Kurniati, Ardesy Melizah; Sarahdeaz, Siti Fazzaura Putri; Zanaria, Rima; Husin, Syarif; Lestari, Hertanti Indah; Yusnita, Heni; Sari, Putri Maya; Yulistiana, Sisca (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Reducing the incidence of stunting is one of the goals of the 2025 Global Nutrition Targets. The prevalence of stunting in children in Indonesia is still high over the last decade. Lack of knowledge on nutritional intake, maternal nutritional status factors, breastfeeding practices, complementary feeding practices, and exposure to infections as well as other factors including education, food system, health care, and sanitation are important determinants of child stunting in Indonesia. This community service activity is carried out with the aim of providing counseling about stunting to mothers and measuring the nutritional status of toddlers as an effort to prevent stunting. The activity was coordinated by students who are members of the Student Executive Board of the Faculty of Medicine, Sriwijaya University (FK Unsri) and Muhammadiyah University (FK UM), involving FK Unsri lecturers, in collaboration with staff at the Puskesmas Taman Bacaan Palembang. At the end of the activity, participants became more aware of the importance of measuring children's nutritional status and stunting prevention measures. There were 6 toddlers who were indicated to be malnourished and reported for management by the Puskesmas team so that they did not progress to stunting.